Another day in the death of America - Younge, Gary (Guardian Books, 2016)
On an average day in America, seven young people aged nineteen or under will be shot dead. Younge chose November 23, 2013, with ten such deaths, and over a period of twenty-four hours reveals the powerful human stories behind the statistics. The result is a gripping chronicle of an ordinary but deadly day in American life, and a series of character portraits of young people taken from us far too soon and those they left behind